Transdiagnostic remission of psychiatric comorbidity in post-traumatic stress disorder, ADHD, and binge-eating disorder using ketogenic metabolic therapy: a retrospective case report - Erin L. Bellamy; Nicole Laurent (Frontiers in Nutrition)
BackgroundPsychiatric comorbidities, including post-traumatic stress disorder (PTSD), ADHD, and binge-eating disorder (BED), frequently share overlapping symptoms and metabolic dysfunctions. Disorder-specific treatments may not adequately address these shared biological mechanisms, resulting in suboptimal outcomes. This case report evaluates ketogenic metabolic therapy (KMT) as an intervention specifically targeting these transdiagnostic features.MethodsA 38 years-old female with PTSD, ADHD, BED, bipolar II disorder, depression, anxiety, and premenstrual dysphoric disorder diagnoses participated in a structured 8 weeks KMT psychoeducation program, with ongoing weekly professional and peer support up to 24 weeks. Standardized assessments, including the PHQ-9, GAD-7, DASS-21, PCL-5, BES, and CRAVED scales, measured symptom severity at baseline and 4 and 12 weeks. Daily biometric data including blood glucose and ketone levels were collected.ResultsBaseline measures indicated severe psychiatric symptoms, notably maximal scores for PTSD and severe binge-eating behavior. By week 12, all psychiatric symptoms resolved evidenced by quantitative reductions to 0 across all validated instruments. The patient consistently reported optimal symptom control when blood ketone levels were maintained between 3 and 5 mmol/L. Qualitative reports substantiated marked functional gains, including improved occupational engagement and social functioning.ConclusionThis report demonstrates the potential of KMT to achieve comprehensive remission in severe, treatment-resistant psychiatric comorbidities. The findings emphasize the necessity for controlled clinical trials to verify optimal therapeutic ketone ranges and establish generalizability across clinical populations experiencing complex psychiatric comorbidities.